2012
DOI: 10.1108/13639511211230101
|View full text |Cite
|
Sign up to set email alerts
|

The Braidwood Commission reports on TASER use in Canada: an evidence‐based policy review

Abstract: PurposeThe purpose of this paper is to review the Braidwood Commission's two reports on the use of TASER conducted energy weapons in Canada and the death of Robert Dziekanski to determine whether the Commission's conclusions and subsequent recommendations constitute sound evidence‐based public policy.Design/methodology/approachThis study analyzes Commissioner Braidwood's eight findings from the first report regarding the medical implications of the use of TASER devices by comparing those findings to the body o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…This puts both suspects and officers at risk. Contemporary evidence has suggested that extreme placement of the TASER on either end of use-of-force continua results in greater rates of injury for both officers and suspects (Alpert & Dunham, 2010; PERF & USDOJ, 2011; Williams, 2012). This finding implies that police agencies with particularly strict or relaxed TASER deployment rules could reduce injuries by restructuring their policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This puts both suspects and officers at risk. Contemporary evidence has suggested that extreme placement of the TASER on either end of use-of-force continua results in greater rates of injury for both officers and suspects (Alpert & Dunham, 2010; PERF & USDOJ, 2011; Williams, 2012). This finding implies that police agencies with particularly strict or relaxed TASER deployment rules could reduce injuries by restructuring their policy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies centered on police TASER use have emerged in recent years, 1 adding new arguments to popular police use-of-force debates (Alpert & Dunham, 2010; Bishopp, Klinger, & Morris, 2015; Chermak, 2009; Crow & Adrion, 2011; DeLone & Thompson, 2009; Ferdik, Kaminski, Cooney, & Sevigny, 2014; Gau, Mosher, & Pratt, 2010; Lin & Jones, 2010; National Institute of Justice (U.S.) [NIJ], 2011; Paoline, Terrill, & Ingram, 2012; Police Executive Research Forum & U.S. Department of Justice [PERF & USDOJ], 2011; Thomas, Collins, & Lovrich, 2011; Williams, 2012). The resulting discussion has revealed a lack of consistency in TASER policy among U.S. police agencies and has raised questions about the TASER’s role in both citizen and officer injuries.…”
mentioning
confidence: 99%
“…In a separate report, the Braidwood Commission, tasked under the Public Inquiry Act of the province of British Columbia to investigate the circumstances surrounding Dziekanski's death, concluded that had the police officers not used Tasers on Dziekanski, he would almost certainly have survived (Braidwood Commission on the Death of Robert Dziekanski, 2010). Although some of the conclusions of the Braidwood Commission have been recently challenged (Williams, 2012), a majority of Canadians (69%) agreed with Justice Braidwood's conclusions (Angus Reid Public Opinion).…”
Section: The Dziekanski Case and The Present Researchmentioning
confidence: 55%
“…Although five separate applications of a CEW were reported (5–9 sec each), with a possible total exposure time of 31 sec, it is unknown whether good contact was established during each application. Williams noted that, when considering CEW applications in general, many suggestions of a causal relationship to death in this high‐profile case have been overstated. There were several other potentially confounding factors, including the struggle with law‐enforcement personnel, stress from both the physical and emotional effects of the alcohol withdrawal, and alcoholic cardiomyopathy .…”
Section: Physiological Factors During Short‐duration Vs Longer‐duratmentioning
confidence: 99%